Evaluation of the impact of microfinance on revenue and the generation of employment in Colombia - Méndez Sayago, Jhon Alexander; Hernández Escolar, Hugo Alfonso; Carreño, Nubia Stella (Cuadernos de Administración, 2011)
The article evaluates the capability of the micro-financial tools to promote revenue improvement in small and medium-sized productive units in Colombia, as well as the creation of jobs in this business segment. For said purpose, estimation was made of the impact of formal credit, of any type of credit, and the credit awarded for participating in entrepreneurial support programs like FOMIPYME. The techniques for the estimation of impact of the treatments (microcredit) comprised: i) the Matching non-parametric estimators of the nearest neighbor and Kernel; ii) the estimator of instrumental variables; and iii) the effect of the local average treatment estimator (LATE). In all the measurements of the effects of the treatment, the null hypothesis was accepted that microcredit does not bear a positive effect on profits and the generation of employment by Micro, Small, and Medium-sized Enterprises.